A hedonic modelling of land property value based on the effect of flooding: a case for peninsular Malaysia - Ismail, Nur Hafizah; Abd Karim, Mohd Zaini; Hasan Basri, Bakti (Springer, 2019)
The effect of flooding on land property value is a major concern of all landowners. Numerous studies have already discussed the risk of potential decline in the value of land property situated in flood-prone areas; however, those that focused on the impact of flooding on land property in Malaysia are still limited. This chapter investigates the effect of flood on the value of agricultural and industrial land properties in Peninsular Malaysia. This chapter’s results suggest that a metre increase in flood depth significantly decreases land property value by 44.6%. This result helps policymakers in designing and developing the policies of land property development that would minimize land property devaluation due to flood depth and help landowners in understanding the effect of flood on land property values.